2002
DOI: 10.1046/j.1365-2427.2002.00843.x
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and seasonal variation in nutrient excretion by benthic invertebrates in a eutrophic reservoir

Abstract: SUMMARY1. Nitrogen (N) and phosphorus (P) fluxes via excretion by benthic invertebrates were quantified in a eutrophic reservoir (Acton Lake, Ohio, U.S.A.). We quantified variation in nutrient fluxes seasonally (June until November 1997), spatially (three sites) and among taxa (chironomids, tubificid oligochaetes and Chaoborus). 2. The three taxa differed in spatial distribution and contribution to nutrient fluxes. Tubificids were the most abundant taxon at two oxic sites (1.5 and 4 m depth), and were exceedin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
75
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(81 citation statements)
references
References 39 publications
5
75
0
1
Order By: Relevance
“…Zoobenthos (chironomids and oligochaetes) was not abundant in central parts of lake Donghu, which were periodically hypoxic during summer and early autumn. The lake Donghu benthic community is typical for eutrophic lake and is dominated by chironomids and oligochaetes (Jonasson, 1984;Devine and Vanni, 2002). In general, we find distribution patterns similar to those reported by previous studies (Chen and Wu, 1990;Wang, 1996;Gong et al, 2000).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Zoobenthos (chironomids and oligochaetes) was not abundant in central parts of lake Donghu, which were periodically hypoxic during summer and early autumn. The lake Donghu benthic community is typical for eutrophic lake and is dominated by chironomids and oligochaetes (Jonasson, 1984;Devine and Vanni, 2002). In general, we find distribution patterns similar to those reported by previous studies (Chen and Wu, 1990;Wang, 1996;Gong et al, 2000).…”
Section: Discussionsupporting
confidence: 89%
“…Interspecies differences in SRP excretion rates were found also in other studies: between the rotifera Euchlanis dilatata (18-19 ºC) and other rotifers (Gulati et al, 1989) as well as between Dreissena polymorpha and D. bugensis (Conroy et al, 2005). At the same time, Devine and Vanni (2002) showed that differences in SRP excretion rate between taxa are not significant and this rate depend mostly on temperature and biomass. Also, it probably might be a result of difference in food resources accumulated in littoral and deepwater sites of the lake, but this question needs future research.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Benthic invertebrates are essential to the transformation of organic matter and nutrient cycling in aquatic environments (Graça, 2001;Devine and Vanni, 2002). The community represents an important component for the understanding of both structure and functioning of aquatic communities, as well as the ecological processes related to hydrological variations (Vannote et al, 1980).…”
Section: Introductionmentioning
confidence: 99%